Exploring Knowledge Entropy in Organizations - BRĂTIANU, Contantin (Management Dynamics in the Knowledge Economy, 2019)
The purpose of this paper is to explore the knowledge entropy processes within organizations and how they are reflected in the knowledge management and organizational intellectual capital. Entropy is a very powerful concept, which can be found today in almost any branch of science and technology. It was introduced by Rudolf Clausius in 1865 in Thermodynamics, then used in the communication theory by Claude Shannon, and expanded by Nicholas Georgescu-Roegen in economics. However, dues to its extensive use in so many different research domains, the concept of entropy became fuzzy and sometimes misleading in applications. Also, its statistical formulations based on the Boltzmann theory made the entropy understanding rather difficult and its interpretations on the edge of coherence. Knowledge entropy is an extension of information entropy and used within the framework of knowledge management. Our conceptual analysis aims to shed light on the appropriate use of knowledge entropy and its potential in knowledge management research and practice. Since knowledge entropy is associated to all transformational processes in knowledge creation, knowledge sharing, knowledge acquisition, and knowledge loss, we may say that knowledge management can be interpreted as the process of managing knowledge entropy within organizations.